TATA CARA PENYELENGGARAAN PESTA HORJA MASYARAKAT MANDAILING - Rosmilan Pulungan (Universitas Negeri Medan, 2020)
Abstract South Tapanuli is one of the Regencies in North Sumatra Province. Ethnicity from this district is called the Mandailing Batak ethnic group, which has various customary activities. Horja godang is a traditional wedding ceremony ceremony for the people of South Tapanuli, where art activities are included (margondang) accompanied by manortor (dancing). Tortor who danced in this activity there are several stages, namely tortor Suhut Bolon, Tortor Kahanggi, Tortor Anak Boru, Tortor Kings of Torbing Balok, Tortor Panusunan Bulung, Tortor Naposo Nauli Bulung, and Tortor Manora Pule. In the presentation, the panor is determined by the kinship system (transfer of natolu) including the order of tortor that must be done. The research method used is a qualitative method. The form of presentation in writing is descriptive analytic. Using this method the results of the research will be described and analyzed with a primary focus on the cultural and social fields. The results of this study are to find out how the procedures for organizing a party for the community of tailings with the customs that apply in the area. Keywords: Custom, Party, Horja